2012
DOI: 10.1136/tobaccocontrol-2012-050531
|View full text |Cite
|
Sign up to set email alerts
|

Particulate mass and polycyclic aromatic hydrocarbons exposure from secondhand smoke in the back seat of a vehicle

Abstract: Context Exposure to secondhand smoke (SHS) has been reduced in the USA by banning smoking in public places. These restrictions have not had the same effect on children's exposure to SHS as adults suggesting that children are exposed to SHS in locations not covered by bans, such as private homes and cars. Objectives Assess exposure to SHS in the backseat of a stationary vehicle where a child would sit, quantify exposures to fine particulates (PM2.5), polycyclic aromatic hydrocarbons (PAH), carbon monoxide (CO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
25
1
3
Order By: Relevance
“…Environmental tobacco smoke exposure in cars can be particularly problematic from a health perspective—especially for children—because the concentration of fine particulate matter in tobacco smoke (ie, airborne mixture of solid particles and liquid droplets <2.5 µm in diameter, referred to as PM 2.5 ) can quickly attain high levels 2 3. WHO air quality guidelines state that to prevent illness, the daily average concentration of PM 2.5 in the air should not exceed 25 µg/m 3 , and the annual average concentration should remain below 10 µg/m 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental tobacco smoke exposure in cars can be particularly problematic from a health perspective—especially for children—because the concentration of fine particulate matter in tobacco smoke (ie, airborne mixture of solid particles and liquid droplets <2.5 µm in diameter, referred to as PM 2.5 ) can quickly attain high levels 2 3. WHO air quality guidelines state that to prevent illness, the daily average concentration of PM 2.5 in the air should not exceed 25 µg/m 3 , and the annual average concentration should remain below 10 µg/m 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…9 Yet Ott et al 7 reported that smoke from only two cigarettes smoked inside a car with the air conditioning on and the windows closed would generate PM 2.5 concentrations of 42 µg/m 3 in a 24-hour period, and others have reported similar findings. 6,10,11 Even with the windows open and the ventilation turned on, average PM 2.5 concentrations during a car ride in which someone is smoking can exceed recommended levels of fine particulate matter. 10 In Quebec, ambient temperatures during the fall and winter months are not conducive to window-lowering.…”
mentioning
confidence: 99%
“…5 SHS exposure in cars can be particularly problematic among children. 6 The concentration of fine particulate matter (i.e., <2.5 micrometres in diameter, referred to as PM 2.5 ) in tobacco smoke can quickly attain high levels in confined spaces. 7,8 WHO guidelines state that to prevent illness, the average daily concentration of PM 2.5 in the air should not exceed 25 µg/m 3 , and annual mean concentration should remain below 10 µg/m 3 .…”
mentioning
confidence: 99%
“…174,175 The levels of polycyclic aromatic hydrocarbons in the vehicles after smoking 3 cigarettes with a window open was higher than measurements made in highly polluted urban traffic or in bars and restaurants where smoking was allowed. 176 After passage of legislation in Maine prohibiting smoking in vehicles when a child is present, smoke-free car policies among households with children and a current smoker increased substantially, from 19.2% to 30.7% (Behavioral Risk Factor Surveillance System data). 177 12.…”
Section: Recommendation Strength: Strong Recommendationmentioning
confidence: 99%